2017
DOI: 10.1111/irel.12191
|View full text |Cite
|
Sign up to set email alerts
|

Output‐Based Performance Pay, Performance‐Support Bias, and the Racial Pay Gap within a Large Retail Stock Brokerage

Abstract: We measure sources of racial inequality in stockbroker pay. Pay differences arise from sales differences. We measure the extent to which sales differences are due to performance‐support bias, whereby African American brokers receive weaker firm supports, or to forces outside the firm, including client access, selection, and consumer discrimination. Data on firm policies are matched to sales results. Data on self‐generation of accounts measure access to wealthy clients. Sales generated from accounts with sales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, Egan et al's (2022) study of financial advisors also examines patterns of punishment according to the ethnicity of the advisor, finding that male advisors with names that indicate either African or Hispanic origin face a punishment gap that is similar to female advisors. Similarly, Madden's research into stockbroking has shown that biases exist against African American brokers (Madden and Vekker, 2017). Other studies in this vein include those by Elvira and Town (2001) and Castilla (2008).…”
Section: Discrimination In Performance Evaluationmentioning
confidence: 99%
“…However, Egan et al's (2022) study of financial advisors also examines patterns of punishment according to the ethnicity of the advisor, finding that male advisors with names that indicate either African or Hispanic origin face a punishment gap that is similar to female advisors. Similarly, Madden's research into stockbroking has shown that biases exist against African American brokers (Madden and Vekker, 2017). Other studies in this vein include those by Elvira and Town (2001) and Castilla (2008).…”
Section: Discrimination In Performance Evaluationmentioning
confidence: 99%
“…Even though pay systems vary between institutional contexts, many organizations apply performance-based or variable pay systems (Eurofound 2016;Madden & Vekker 2017). Yearly performance appraisal is a response to organizations' quest to systematically measure both what the employee has achieved and how the task was carried out (Storey & Sisson 2005).…”
Section: Pricing Prizing and (Ap)praising Labormentioning
confidence: 99%
“…The above hypotheses relate to actual performance differences, which should be relatively clear where incentives consist of commissions and piece-rates. Even so, differences in assignments and judgements about whether quality standards have been met create some room for discretion and non-performance-based inequalities (Fang and Heywood, 2006;Madden, 2012), as can customer discrimination in service jobs (Madden and Vekker, 2017). Bonus pay, classed in the WES as an incentive, also tends to be discretionary (Elvira and Graham, 2002).…”
Section: Compensation Schemesmentioning
confidence: 99%